Environmental variability at a marine cage culture operation in the Matanchén Bay, SE Gulf of California, Mexico - Arámbul, Eulalio; Castillo-Vargasmachuca, Sergio G.; Ponce-Palafox, Jesús T.; Páez-Osuna, Federico; Arredondo-Figueroa, José Luis; Esparza-Leal, Héctor M. (Revista de Biología Marina y Oceanografía, 2018)
This study investigated the environmental impact of offshore floating sea cages and the influence of runoff on cage fish farming in SE Gulf of California via the analysis of the physico-chemical profiles of the water column and sediments, located in SE Gulf of California, Mexico. Water and sediment samples were analyzed for physico-chemical parameters. In general, nitrates showed the highest concentrations of nutrients in the potential impact station (1.92 mg L-1). The results displayed temporal variations in the NH4+, NO3-, and PO43- in the water column as well as variations in the clay and organic matter in the sediment. The observed trends of these parameters were toward higher concentration in the potential impact and control stations.